HOAX DAN LOGIKA BAHASA: FENOMENA NIAT BAIK DIMANFAATKAN UNTUK TIPU MUSLIHAT - Rufus Goang Swaradesy (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2020)
In this paper, the author tries to analyze the phenomenon of hoax associated with language logic. A hoax is a deceit that can influence the negative perceptions. Negatif perception will cause emergence of the negative impact of other. The hoax is a way of thinking problem and logic used to solve it. The results, good logic is a weapons to ward off hoax.